1997
DOI: 10.1002/(sici)1097-0266(199702)18:2<111::aid-smj856>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

In the Eyes of the Beholder: Conceptualizations of Relatedness Held by the Managers of Large Diversified Firms

Abstract: In this study, chief executive officers were surveyed to evaluate how they perceive their firms’ businesses to be related. Responses from nearly 200 top executives provided the data for this study. Findings suggest that some managers think of relatedness in terms of similarities in products, markets, and technologies, a type of relatedness that is assessed by existing measures of diversification. The study also found, however, that managers hold additional conceptualizations of relatedness, including relatedne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 6 publications
(9 reference statements)
1
69
0
1
Order By: Relevance
“…Criterion (4) is addressed implicitly by building the index on a census of all firms in the US manufacturing economy down to firms with three employees. The importance of criterion (4) is suggested by the work of Stimpert and Duhaime (1997) and Pehrsson (2006), who have shown that conceptualizations of relatedness are multidimensional by analyzing managers' answers to a series of questions about the relationships between their businesses. The…”
Section: Issues In Developing a General Relatedness Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Criterion (4) is addressed implicitly by building the index on a census of all firms in the US manufacturing economy down to firms with three employees. The importance of criterion (4) is suggested by the work of Stimpert and Duhaime (1997) and Pehrsson (2006), who have shown that conceptualizations of relatedness are multidimensional by analyzing managers' answers to a series of questions about the relationships between their businesses. The…”
Section: Issues In Developing a General Relatedness Indexmentioning
confidence: 99%
“…Herfindahl and entropy measures are strongly correlated to product market conceptualizations of relatedness, but other conceptualizations-such as financial, or commodity relatedness-are inadequately measured by standard indices (Stimpert and Duhaime, 1997). If these other conceptualizations are systematically employed by managers in actual diversification moves (e.g.…”
Section: Issues In Developing a General Relatedness Indexmentioning
confidence: 99%
“…Importantly, such observations strongly imply that a firm's strategy development in general does not follow sudden and unanticipated changes (Stuart and Podolny, 1996). Current research, moreover, acknowledges multiple and interacting bases of perceived relatedness (Farjoun, 1998;Stimpert and Duhaime, 1997) where physical and resource attributes can appropriately be employed in studying perceived relatedness and its effects on performance. The physical base concerns relations between apparent product characteristics, whereas the resource base pays attention to skills and other key resources.…”
Section: Relatedness and Performance Of The Establishmentmentioning
confidence: 99%
“…The indices presented capture a multidimensional concept (Pehrsson 2006, Stimpert & Duhaime 1997, but are free of researchers' bias since they will not require combining different elements of relatedness into an index with predefined weights (Lien & Klein, 2009). The indices proposed however are not context free.…”
Section: Discussionmentioning
confidence: 99%
“…Firms resort to local search in the development of organizational routines and more broadly organizational learning (e.g., Levitt & March, 1988;March, 1991;Nelson & Winter, 1982;Simon, 1991). Research in the 'upper echelons' tradition (e.g., Carpenter, Geletkanycz, & Sanders, 2004;Hambrick & Mason, 1984) has also demonstrated that top managers' background, experiences, and values influence strategic decisions including corporate change (Goodstein, Gautam, & Boeker, 1994), product diversification (Farjoun & Lai, 1997;Pehrsson, 2006;Stimpert & Duhaime, 1997), international diversification (Tihanyi, Ellstrand, Daily, & Dalton, 2000), and product innovation (Tripsas & Gavetti, 2000).…”
Section: Literature Review Local Search Anchoring and Decision Makingmentioning
confidence: 99%